2017
DOI: 10.1080/14767058.2017.1330879
|View full text |Cite
|
Sign up to set email alerts
|

Assessing infant-oriented care with developmental support approach in Iranian NICUs

Abstract: The low mean score of infant-centered developmental care implies health staff's focus on neonatal care with at least the quality of care and its impact on development in preterm infants, and inadequate attention to the infant as an active member in care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…To help improve clinical outcomes for small and sick newborns, a culture of capability should be promoted in places where fatalism on the part of healthcare providers is common [ 62 , 63 ]. Evidence from high- and middle-income countries has also demonstrated the value of family-centered developmental care for this vulnerable population [ 64 66 ]. A study in Colombia found that continuing education for care providers, provision of materials for positioning of neonates, and use of an informative video for parents were helpful in promoting related care practices [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…To help improve clinical outcomes for small and sick newborns, a culture of capability should be promoted in places where fatalism on the part of healthcare providers is common [ 62 , 63 ]. Evidence from high- and middle-income countries has also demonstrated the value of family-centered developmental care for this vulnerable population [ 64 66 ]. A study in Colombia found that continuing education for care providers, provision of materials for positioning of neonates, and use of an informative video for parents were helpful in promoting related care practices [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study design was a multicenter cluster clinical trial with a control group. Four hospitals with matched neurodevelopmental care (13)(14)(15) were selected using a random cluster sampling method. Then, 72 dead mother-infant cases who met the inclusion criteria were selected by means of a purposive sampling technique.…”
Section: Methodsmentioning
confidence: 99%
“…To be able to provide quality care for preterm infants, the NICU nurses should possess current and accurate knowledge and skills, as well as the perception that such care is important in the context of prematurity 11. However, several previous studies conducted in Iran and India have reported that the level of knowledge related to developmentally supportive care for premature infants in NICU nurses is not high 11–13. Therefore, it is necessary to assess NICU nurses' knowledge concerning developmentally supportive care to ensure high-quality healthcare for premature infants.…”
Section: Background and Significance/literature Reviewmentioning
confidence: 99%
“…11 However, several previous studies conducted in Iran and India have reported that the level of knowledge related to developmentally supportive care for premature infants in NICU nurses is not high. [11][12][13] Therefore, it is necessary to assess NICU nurses' knowledge concerning developmentally supportive care to ensure high-quality healthcare for premature infants.…”
mentioning
confidence: 99%